Astaxanthin Inhibits Mitochondrial Permeability Transition Pore Opening in Rat Heart Mitochondria - Yulia Baburina; Roman Krestinin; Irina Odinokova; Linda Sotnikova; Alexey Kruglov; Olga Krestinina (MDPI AG, 2019)
The mitochondrion is the main organelle of oxidative stress in cells. Increased permeability of the inner mitochondrial membrane is a key phenomenon in cell death. Changes in membrane permeability result from the opening of the mitochondrial permeability transition pore (mPTP), a large-conductance channel that forms after the overload of mitochondria with Ca2+ or in response to oxidative stress. The ketocarotenoid astaxanthin (AST) is a potent antioxidant that is capable of maintaining the integrity of mitochondria by preventing oxidative stress. In the present work, the effect of AST on the functioning of mPTP was studied. It was found that AST was able to inhibit the opening of mPTP, slowing down the swelling of mitochondria by both direct addition to mitochondria and administration. AST treatment changed the level of mPTP regulatory proteins in isolated rat heart mitochondria. Consequently, AST can protect mitochondria from changes in the induced permeability of the inner membrane. AST inhibited serine/threonine protein kinase B (Akt)/cAMP-responsive element-binding protein (CREB) signaling pathways in mitochondria, which led to the prevention of mPTP opening. Since AST improves the resistance of rat heart mitochondria to Ca2+-dependent stress, it can be assumed that after further studies, this antioxidant will be considered an effective tool for improving the functioning of the heart muscle in general under normal and medical conditions.